138k views
1 vote
find the equation of the pair of lines perpendicular to the lines pair represented by the equation ax^2-2hxy+by^2=0 and passing through the origin.​

User Youssof
by
4.8k points

1 Answer

1 vote

The equation of the pair of lines perpendicular to the lines given equation is
b x^(2)-2 h x y+a y^(2)=0.

Solution:

Given equation is
a x^(2)+2 h x y+b y^(2)=0.

Let
m_1 and
m_2 be the slopes of the given lines.

Sum of the roots =
-\frac{\text {coefficient of } x y}{\text {coefficient of } y^(2)}


$m_1+m_2=(-2h)/(b) – – – – – (1)

Product of the roots =
-\frac{\text {coefficient of } x^2}{\text {coefficient of } y^(2)}


$m_1 \cdot m_2=(a)/(b) – – – – – (2)

The required lines are perpendicular to these lines.

Slopes of the required lines are
$-(1)/(m_(1)) \text { and }-(1)/(m_(2))

Required lines also passes through the origin,

therefore their y-intercepts are 0.

Hence their equations are:


$y=-(1)/(m_(1))x \text { and }y=-(1)/(m_(2))x

Do cross multiplication, we get


m_1y=-x \ \text{and} \ m_2y=-x

Add x on both sides of the equation, we get


x+m_1y=0 \ \text{and} \ x+m_2y=0

Therefore, the joint equation of the line is


\left(x+m_(1) y\right)\left(x+m_(2) y\right)=0


x^2+m_2xy+m_1xy+m_1m_2y^2=0


x^(2)+\left(m_(1)+m_(2)\right) x y+m_(1) m_(2) y^(2)=0

Substitute (1) and (2), we get


$x^(2)+\left((-2 h)/(b)\right) x y+\left((a)/(b)\right) y^(2)=0

To make the denominator same, multiply and divide first term by b.


$ (b)/(b) x^(2)+\left((-2 h)/(b)\right) x y+\left((a)/(b)\right) y^(2)=0


$(bx^2-2hxy+ay^2)/(b) = 0

Do cross multiplication, we get


b x^(2)-2 h x y+a y^(2)=0

Hence equation of the pair of lines perpendicular to the lines given equation is
b x^(2)-2 h x y+a y^(2)=0.

User DariusL
by
5.1k points